Ground state depletion nanoscopy resolves semiconductor nanowire barcode segments at room temperature - Oracz, Joanna; Hell, Stefan (Nano letters, 2017)
Nanowires hold great promise as tools for probing and interacting with various molecular and biological systems. Their unique geometrical properties (typically <100 nm in diameter and a few micrometers in length) enable minimally invasive interactions with living cells, so that electrical signals or forces can be monitored. All such experiments require in situ high-resolution imaging to provide context. While there is a clear need to extend visualization capabilities to the nanoscale, no suitable super-resolution far-field photoluminescence microscopy of extended semiconductor emitters has been described. Here, we report that ground state depletion (GSD) nanoscopy resolves heterostructured semiconductor nanowires formed by alternating GaP/GaInP segments (“barcodes”) at a 5-fold resolution enhancement over confocal imaging. We quantify the resolution and contrast dependence on the dimensions of GaInP photoluminescence segments and illustrate the effects by imaging different nanowire barcode geometries. The far-red excitation wavelength (∼700 nm) and low excitation power (∼3 mW) make GSD nanoscopy attractive for imaging semiconductor structures in biological applications.
Gesehen am 25.10.2018